Reconceptualization of the Erlangen Score for the Assessment of Dementia Risk: The ERlangen Score - Utz, Janine; Olm, Pauline; Jablonowski, Johannes; Siegmann, Eva-Maria; Spitzer, Philipp; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Journal of Alzheimer's Disease, 2023)
BACKGROUND: The established Erlangen Score (ES) for the interpretation of cerebrospinal fluid (CSF) biomarkers in the diagnostics of Alzheimer's disease (AD) uses markers of amyloidopathy and tauopathy, equally weighted to form an easy-interpretable ordinal scale. However, these biomarkers are not equally predictive for AD. OBJECTIVE: The higher weighting of the Aβ42/Aβ40 ratio, as a reconceptualized ERlangen Score (ERS), was tested for advantages in diagnostic performance. METHODS: Non-demented subjects (N = 154) with a mean follow up of 5 years were assigned to a group ranging from 0 to 4 in ES or ERS. Psychometric trajectories and dementia risk were assessed. RESULTS: The distribution of subjects between ES and ERS among the groups differed considerably, as grouping allocated 32 subjects to ES group 2, but only 2 to ERS group 2. The discriminative accuracy between the ES (AUC 73.2%, 95% CI [64.2, 82.2]) and ERS (AUC 72.0%, 95% CI [63.1, 81.0]) for dementia risk showed no significant difference. Without consideration of the Aβ42/Aβ40 ratio in ES grouping, the optimal cut-off of the ES shifted to ≥2. CONCLUSIONS: The ERS showed advantages over the ES in test interpretation with comparable overall test performance, as fewer cases were allocated to the intermediate risk group. The established cut-off of ≥2 can be maintained for the ERS, whereas it must be adjusted for the ES when determining the Aβ42/Aβ40 ratio.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Alzheimer’s disease; dementia risk; Erlangen Score; longitudinal study; neuropsychological trajectories